Preparation, Modification, Characterization and Antioxidant Activities of Apigenin Liposomes - Siyu DAI; Ying TANG; Nian LIU; Lu HE; Miao GU; Chenbo FENG; Jin REN; Zhengjie FANG (Shipin gongye ke-ji)
Objective: To improve the water solubility and stability of apigenin and promote its antioxidant biological activity, apigenin liposomes (AP-L) were developed and subsequently surface-modified with chitosan (CS). Methods: The appropriateness of two methods, low-speed centrifugation and membrane filtration, for measuring encapsulation efficiency was evaluated. Encapsulation efficiency served as the evaluation criterion to compare the AP-L preparation methods employing the film dispersion-ultrasound and ethanol injection-ultrasound techniques. Additionally, the preparation process underwent optimization via both single-factor experiments and response surface tests. Chitosan was adsorbed onto the surface of liposomes through electrostatic adsorption to produce chitosan apigenin liposomes (CS-AP-L). The appearance, microstructure, particle size and distribution, potential, encapsulation efficiency and stability of the liposomes were observed before and after chitosan modification. The antioxidant capacity of apigenin dispersion (AP-D), AP-L and CS-AP-L was investigated by DPPH and ABTS+ free radical scavenging assays. Results: The low-speed centrifugation method was found to be more precise in determining the entrapment efficiency of liposomes, while the membrane dispersion-ultrasonic method demonstrated higher encapsulation efficiency. The optimal preparation process for AP-L included 6 mg of apigenin, an apigenin to phospholipid ratio of 1:24, a phospholipid to cholesterol ratio of 6:1, 6.3 mL of ethanol, 20 mL of phosphate buffer solution (PBS), hydration temperature 50 ℃ and ultrasonic time 20 min. The particle size of AP-L was 157.34±1.87 nm, the polydispersity index (PDI) was 0.240±0.025, and the encapsulation efficiency was 66.50%±1.00%. The particle size of CS-AP-L increased to 564.22±39.7 nm, the PDI was 0.292±0.022, and the encapsulation efficiency decreased to 60.17%±1.97%. After being stored at room temperature for 30 days, the leakage rate of AP-L was 21.92%±4.84%, compared to 10.64%±0.28% for CS-AP-L. This indicated that CS-AP-L demonstrated superior stability. Furthermore, the DPPH and ABTS+ free radical scavenging experiment demonstrated that both AP-L and CS-AP-L could enhance the free radical scavenging capacity of apigenin, with CS-AP-L showing even greater scavenging capability. Conclusion: The CS-AP-L prepared in this study exhibits appropriate particle size, uniform distribution, high encapsulation efficiency, good stability, and the capability to enhance the antioxidant activities of apigenin, thereby offering valuable insights for the development of apigenin derivative products.